The chemical journey of Europium(III) through winter rye (Secale cereale L.) – Understanding through mass spectrometry and chemical microscopy. (February 2023) - Stadler, Julia; Vogel, Manja; Steudtner, Robin; Drobot, Björn; Kogiomtzidis, Anna L.; Weiss, Martin; Walther, Clemens
Abstract: A combination of biochemical preparation methods with microscopic, spectroscopic, and mass spectrometric analysis techniques as contemplating state of the art application, was used for direct visualization, localization, and chemical identification of europium in plants. This works illustrates the chemical journey of europium (Eu(III)) through winter rye ( Secale cereale L.), providing insight into the possibilities of speciation for Rare Earth Elements (REE) and trivalent f-elements. Kinetic experiments of contaminated plants show a maximum europium concentration in Secale cereale L. after four days. Transport of the element through the vascular bundle was confirmed with Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray analysis (EDS). For chemical speciation, plants were grown in a liquid nutrition medium, whereby Eu(III) species distribution could be measured by mass spectrometry and luminescence measurements. Both techniques confirm the occurrence of Eu malate species in the nutrition medium, and further analysis of the plant was performed. Luminescence results indicate a change in Eu(III) species distribution from root tip to plant leaves. Microscopic analysis show at least three different Eu(III) species with potential binding to organic and inorganic phosphate groups and a Eu(III) protein complex. With plant root extraction, further europium species could be identified by using Electrospray Ionization Mass Spectrometry (ESI MS). Complexation with malate, citrate, a combined malate-citrate ligand, and aspartate was confirmed mostly in a 1:1 stoichiometry (Eu:ligand). The combination of the used analytical techniques opens new possibilities in direct species analysis, especially regarding to the understanding of rare earth elements (REE) uptake in plants. This work provides a contribution in better understanding of plant mechanisms of the f-elements and their species uptake. Graphical abstract: Image 1 Highlights: Spectroscopic, microscopic, and mass spectrometric methods were used to identify the journey of Eu(III) in Secale cereale L. Imaging of the plant part samples showed different distributions of Eu(III) species in the plant tissue. First possible Eu(III) species were identified in Secale cereale L. by ESI MS and TRLFS.